The Question of Alterity: the Bitter Life of the Guaraní Tupã According to the White Man's Literature and to the Mbyá's Lively Oral Version - Ruiz, Irma (2009)
For centuries, a part of the cultured world heeded the White man views on the Guaraní thoughts and behavior —those were the exclusive times of Anthropology of the Other. Nowadays there are attempts to do Anthropology of the Other on ourselves. In order to show both sides of this issue, this paper compares the voices of some White scholars who wrote about the Guaraní with some of the Mbyá-guaraní talking about their own and the White man culture. The topic in question is the figure of Tupã , whose name was appropriated by the colonial missionaries to build their monotheistic discourse. In this interplay of alterity, we analyze first the pernicious “literary life” of this character, followed by the voices of those still hurting from this historic event. This confrontation reveals both the biased inconsistencies of some Guaraní writings and strategies to protect their polytheism, and the magnitude of the symbolic violence intrinsic to the Evangelization process.